Critical combinations of shear and longitudinal direct stress for long plates with transverse curvature - Batdorf, S. B.; Schildcrout, Murry; Stein, Manuel (National Advisory Committee for Aeronautics, 1947)
A theoretical solution is presented for the buckling stresses of long plates with transverse curvature loaded in shear and longitudinal direct stress. The theoretical critical-stress combinations for plates having either simply supported or clamped edges are given in figures and tables and a comparison is made with a previous theoretical solution for simply supported plates.
"Langley Memorial Aeronautical Laboratory."
Date of issue: June 1947.
Report no. NACA TN No. 1347.
Keywords: Plates (Engineering); Strains and stresses.; Buckling (Mechanics); Loads (Mechanics); Shear (Mechanics); elektronické knihy; electronic books